EFEKTIVITAS LATIHAN SMALL SIDED GAMES DALAM MENINGKATKAN KEBUGARAN JASMANI PEMAIN FUTSAL USIA SEKOLAH: STUDI EKSPERIMEN - Fazar Alfarizi; Oman Hadiana (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
the physical fitness level of students participating in the futsal extracurricular program at SMP PGRI 1 Ulujami Pemalang. This research employed an experimental method with a one group pretest-posttest design. The research subjects consisted of 34 students involved in the futsal extracurricular activity. Physical fitness levels were measured using the Indonesian Physical Fitness Test (TKJI). Data analysis was conducted through prerequisite tests, including normality and homogeneity tests, followed by hypothesis testing using the Paired Sample t-Test. The results showed an improvement in students’ physical fitness after implementing Small Sided Games training, indicated by an increase in the mean score from 16.15 in the pretest to 19.24 in the posttest. The hypothesis test obtained a significance value of 0.000 < 0.05, indicating a significant difference between before and after the treatment. Therefore, Small Sided Games training is effective in improving students’ physical fitness and can be used as an alternative game-based futsal training method.